Intellectual Property in Pharmaceutical Industry - Pospíšil, Kristián; Štěrbová, Ludmila, 1957-; Müller, David, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The aim of the thesis is to analyze the modes of protection of pharmaceutical patents in an international trade from the viewpoint of both research oriented pharmaceutical and generic pharmaceutical company. More specifically, what are the steps needed to ensure the protection of a pharmaceutical in an international environment. Secondly, it is scrutinised what economic benefits such protection has and how it may impact the developing countries as the patent provides the patent owner with monopoly that lies in the exclusive time-bound production of the medicament. Thirdly, it is examined how the International community and organizations cope with the protection of pharmaceutical patents if such protection brings about negative effects on public health.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses